2019
DOI: 10.1101/537381
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

VAMPr: VAriant Mapping and Prediction of antibiotic resistance via explainable features and machine learning

Abstract: Antimicrobial resistance (AMR) is an increasing threat to public health. Current methods of determining AMR rely on inefficient phenotypic approaches, and there remains incomplete understanding of AMR mechanisms for many pathogen-antimicrobial combinations. Given the rapid, ongoing increase in availability of high density genomic data for a diverse array of bacteria, development of algorithms that could utilize genomic information to predict phenotype could both be useful clinically and assist with discovery o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The method gave good performances (94e99% correct predictions) in E. coli, K. pneumoniae and Acinetobacter baumannii. The authors provided a proof-of-concept of the test directly from positive blood cultures with a turn-around time of <4 h. Other ML systems used WGS to combine the identification and antibiotic susceptibility testing of microorganisms: Drouin et al reported an ML system that can identify 12 species and susceptibility to 56 antibiotics [61], Kim et al nine species and 29 antibiotics [62].…”
Section: Evaluation Of Antimicrobial Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The method gave good performances (94e99% correct predictions) in E. coli, K. pneumoniae and Acinetobacter baumannii. The authors provided a proof-of-concept of the test directly from positive blood cultures with a turn-around time of <4 h. Other ML systems used WGS to combine the identification and antibiotic susceptibility testing of microorganisms: Drouin et al reported an ML system that can identify 12 species and susceptibility to 56 antibiotics [61], Kim et al nine species and 29 antibiotics [62].…”
Section: Evaluation Of Antimicrobial Susceptibilitymentioning
confidence: 99%
“…Moreover, the systems still required the most time-consuming step in the diagnosis which is the technical manipulation of the stools (fresh state, concentrations, preparations, colourations). In bacteriology, most ML systems targeted either bacterial identification or antibiotic susceptibility testing for a limited number of species (median 3, IQR 7e15), but optimal tools should be able to perform different tasks on a broad scope of species using the same data, as has been done in some recent articles [61,62].…”
Section: For Current and Future Datamentioning
confidence: 99%
“…The lengthy nature of conventional methods for bacterial identification and susceptibility testing purposes has resulted in the empirical use of broad-spectrum antibiotics and led to the spread of resistance [85]. Aiming at rapid and reliable detection of AMR, numerous studies have recently been reported on the use of ML algorithms in combination with the output of several analytical techniques, such as MALDI-TOF MS [89,96,[110][111][112][113][114][115][116][117][118], vibrational spectroscopy [102,103,119], whole-genome sequencing [120][121][122][123][124], a microscopy-based platform [125], and acousticenhanced flow cytometry [126].…”
Section: Detection Of Antimicrobial Resistancementioning
confidence: 99%
“…The authors showed that the predictive accuracy of the applied tree models was the lowest for resistance to third-line drugs such as para-aminosalicylic acid and Dcycloserine (AUROC below 0.85) and highest for resistance to first-line drugs such as amikacin, ciprofloxacin, kanamycin, moxifloxacin, and multi-drug resistant tuberculosis (AUROC above 0.96). Furthermore, a novel bioinformatic tool for variant mapping and prediction of antibiotic resistance (VAMPr) has been reported by Kim et al [124] with a mean accuracy of 91.1% for all antibiotic-pathogen combinations.…”
Section: Detection Of Antimicrobial Resistancementioning
confidence: 99%
“…The e ux proteins are responsible for multi-drug resistance in many microbial pathogens [1][2][3][4][5] . In the past several highly accessed and useful antibiotic resistance databases have been established to catalogue the known antibiotic resistance genes at both the whole genome as well as at genes/proteins levels [6][7][8][9][10][11][12][13][14][15] . But an in-silico tool to predict and annotate e ux proteins responsible for antibiotic resistance (ARE) has not been developed yet.…”
Section: Introductionmentioning
confidence: 99%